Visceral abdominal fat accumulation predicts the conversion of metabolically healthy obese subjects to an unhealthy phenotype - Hwang, Y-C; Hayashi, T; Fujimoto, W Y; Kahn, S E; Leonetti, D L; McNeely, M J; Boyko, E J (International Journal of Obesity, 2015)
Background: A proportion of obese subjects appear metabolically healthy (MHO) but little is known about the natural history of MHO and factors predicting its future conversion to metabolically unhealthy obese (MUO). Objectives: The aim was to determine prospectively the frequency of conversion of MHO to MUO and the clinical variables that independently predicted this conversion, with a particular focus on the role of body composition. Methods: We identified 85 Japanese Americans with MHO (56 men, 29 women), aged 34–73 years (mean age 49.8 years) who were followed at 2.5, 5 and 10 years after enrollment with measurements of metabolic characteristics, lifestyle and abdominal and thigh fat areas measured by computed tomography. Obesity was defined using the Asian body mass index criterion of ⩾25 kg m −2 . Metabolically healthy was defined as the presence of ⩽2 of 5 metabolic syndrome components proposed by the National Cholesterol Education Program Adult Treatment Panel III, while metabolically unhealthy was defined as ⩾3 components. Results: Over 10 years of follow-up, 55 MHO individuals (64.7%) converted to MUO. Statistically significant univariate predictors of conversion included dyslipidemia, greater insulin resistance and greater visceral abdominal (VAT) and subcutaneous abdominal fat area (SAT). In multivariate analysis, VAT (odds ratio per 1-s.d. increment (95% confidence interval) 2.04 (1.11–3.72), P =0.021), high-density lipoprotein (HDL) cholesterol (0.24 (0.11–0.53), P <0.001), fasting plasma insulin (2.45 (1.07–5.62), P =0.034) and female sex (5.37 (1.14–25.27), P =0.033) were significantly associated with future conversion to MUO. However, SAT was not an independent predictor for future conversion to MUO. Conclusions: In this population, MHO was a transient state, with nearly two-thirds developing MUO over 10 years, with higher conversion to MUO independently associated with VAT, female sex, higher fasting insulin level and lower baseline HDL cholesterol level.